2021
DOI: 10.5947/jeod.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intermediation in Innovation: A Study of Multilayered Contexts and Embedded Dynamics of Organisation-Creation

Abstract: The article is based on a theoretical exploration and empirical analysis of formalized public initiated instruments-eight network entrepreneurs-intended to promote, intermediate and support innovation and entrepreneurship in firms and firm networks located in three different business areas in Mid-Norway: food value chain, experience industries, and renewable energy and environmental technology. The article intends to explore how the intermediation perspectives in innovation theory could be combined with the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…This touches on ideas expressed by Steyaert and Hjorth (2003, p. 9), who posited that entrepreneurship, in all its forms, "creates channels for peoples' energies and directs these energies into efforts of differentiation," and that the entrepreneurial process has been described as a way of "channeling desire" into new or productive ends (Hjorth, 2014). Although this idea of channeling desire requires some ontological elaboration (e.g., within a Deleuzian framework as in Hjorth, 2009;Sletterød, Carlsson & Hjorth, 2021), it could also be mistaken for a quasi-magical ability possessed by the entrepreneur. However, as the above instance elucidated, being committed or invested in the initiative of creating Konsthall Tornedalen has also been experienced as way of being invested in the village.…”
Section: Dare Not Stop Hopingmentioning
confidence: 96%
See 2 more Smart Citations
“…This touches on ideas expressed by Steyaert and Hjorth (2003, p. 9), who posited that entrepreneurship, in all its forms, "creates channels for peoples' energies and directs these energies into efforts of differentiation," and that the entrepreneurial process has been described as a way of "channeling desire" into new or productive ends (Hjorth, 2014). Although this idea of channeling desire requires some ontological elaboration (e.g., within a Deleuzian framework as in Hjorth, 2009;Sletterød, Carlsson & Hjorth, 2021), it could also be mistaken for a quasi-magical ability possessed by the entrepreneur. However, as the above instance elucidated, being committed or invested in the initiative of creating Konsthall Tornedalen has also been experienced as way of being invested in the village.…”
Section: Dare Not Stop Hopingmentioning
confidence: 96%
“…They also adopted a Deleuzian framing in their conception of desire, which gave them an ontology whereby entrepreneurship became a device for creating vessels "towards which desire can flow" (Dey, Schneider & Maier, 2016, p. 1452. This language also ties back into how some scholars who have drawn on a Deleuzian understanding of desire have suggested that entrepreneurship is about "channeling" desire into sociality (e.g., Hjorth, 2014a;Sletterød, Carlsson & Hjorth, 2021). Although this philosophical vocabulary may open up new vistas for seeing desire and its relation to entrepreneurship, it can also be criticized for being overly abstract because metaphysical ideas about the production of desire can be difficult to translate into practice.…”
Section: Desire and Ontological Commitmentsmentioning
confidence: 99%
See 1 more Smart Citation